2018
DOI: 10.1212/wnl.0000000000005418
|View full text |Cite
|
Sign up to set email alerts
|

Disability in adults with arthrogryposis is severe, partly invisible, and varies by genotype

Abstract: This study describes disability patterns of a cohort of adults with AMC by genotype. The disability of adults with AMC is influenced by genotype, with important invisible disability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
49
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(52 citation statements)
references
References 21 publications
3
49
0
Order By: Relevance
“…These studies suggest that some sort of ambulation is important, especially in the home. The most preferred indoor mobility is walking either independently or with gait aids, however, outdoor mobility is often using wheelchairs or scooters (Dai et al, ; Steen et al, ). The need for ambulation within the home means that the emphasis during childhood to obtain functional foot, knee, and hip positioning for minimal standing and walking is desired.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies suggest that some sort of ambulation is important, especially in the home. The most preferred indoor mobility is walking either independently or with gait aids, however, outdoor mobility is often using wheelchairs or scooters (Dai et al, ; Steen et al, ). The need for ambulation within the home means that the emphasis during childhood to obtain functional foot, knee, and hip positioning for minimal standing and walking is desired.…”
Section: Discussionmentioning
confidence: 99%
“…People with AMC, as they get older, experience significant chronic pain (Jones, Miller, Street, & Sawatzky, ). Thirty‐nine out of 43 people with AMC had chronic pain in Dai et al's study (Dai et al, ). They also reported that 34% felt chronic fatigue and 43% experienced anxiety, both of which may be a result of chronic pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is uncertain whether the respiratory complications are age‐dependent. Beals and Weleber () gave a detailed account in a large case series of four generations of a single family with DA5 with pulmonary issues, where some patients had severe mixed obstructive‐restrictive pulmonary dysfunction, and even decreased pulmonary function from a young age whom eventually required BiPAP at night, however, these reports mention cases severe enough to necessitate a tracheostomy (Dai et al, ). The restrictive pulmonary problems could be aggravated because of vertebral malalignment (Dai et al, ; Okubo et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Following the first two symposia, there was agreement that emphasis should be placed on collecting information about the natural history into adulthood on each disorder, and to develop mechanisms for evaluation, classification, and utilizing consistent procedures. Since then, progress was made in gaining a better understanding of outcomes in adults with AMC (Dai et al, ; Nouraei, Sawatzky, MacGillivray, & Hall, ) and a pain and disability index was validated for adults with AMC (Jones, Miller, Street, & Sawatzky, ). In addition, a research platform for children with AMC in North America (Dahan‐Oliel et al, ) and an international longitudinal registry for adults were funded in 2017 and data collection is currently underway (Sawatzky et al, ).…”
Section: Introductionmentioning
confidence: 99%